Juridical Analysis of Requirements for Candidates for Village Apparatus Based on Bojonegoro Regency Regional Regulation Number 4 of 2019 concerning Village Apparatus Juncto Minister of Home Affairs Regulation Number 67 of 2017 concerning Appointment and D - Adi Herisasono; Ferdiati Ferdiati; Mochammad Fadil; Romiyatul Fatlah (Fakultas Hukum Dehasen, 2023)
Completion of village officials is a routine agenda that is usually held in a democratic system in village governance. This is a form of local democracy, namely the implementation of democracy at the village level, the democratic appointment of village officials promises the establishment of a representative government. Law No. 6 of 2014 requires that the appointment of village officials in Article 50 letter (c) is domiciled in the local village or at least resides at least 1 (one) year before registration. Whereas in the Regional Regulation of Bojonegoro Regency Number 4 of 2019 the appointment of village officials does not require that they have to live in the local village. Based on the elaboration above, the authors take the following formulation of the problem: What are the arrangements for filling in village officials according to Law Number 6 of 2014 and Minister of Home Affairs Regulation Number 67 of 2017? The purpose of this study was to find out the filling arrangements for village officials according to Law Number 6 of 2014 and Minister of Home Affairs Regulation Number 67 of 2017. normative law in the form of literature review which is carried out by tracing primary and secondary legal materials, which is carried out through a study of statutory regulations and other legal materials. Law Number 6 of 2014 and Minister of Home Affairs Regulation Number 67 of 2017 have the same conditions for appointing village officials, namely they must be registered as villagers. As explained in Article 50 paragraph (1) letter c of Law Number 6 of 2014 and Article 2 paragraph (1) of the Minister of Home Affairs Regulation Number 67 of 2017. This requirement is intended to ensure that prospective village officials understand the character and culture of village communities. Article 2 Paragraph (1) Bojonegoro Regency Regional Regulation Number 4 of 2019 is not in line with the aforementioned Law and Permendagri. As a community that is given the right to govern, village government should not be equated with the logic of regional or national head government. In addition, there are concerns about the potential for exploitation of village resources for the personal interests of village elites if government positions or village officials are filled by people who do not come from or live in the village and do not know the ins and outs of the village.